The role of Kalmyk settlers from the Russian gubernies in the socio-economic development of the Kalmyk Autonomous region in the 1920s - B. A. Erdneeva; E. N. Badmaeva (Nomadic Civilization: Historical Research, 2023)
The presented scientific study examines the history of the emergence of Kalmyks in Russian provinces and regions, their daily life outside the Kalmyk steppe, both in the imperial period and in the first post-revolutionary years. An attempt is made to analyze the many years of socio-economic experience accumulated by them during their long residence in other Russian regions, which later, after migrating and moving to the Kalmyk Autonomous Region in the early and mid-1920s, played an important role in the socio-economic development of the steppe region. The reasons that caused the spontaneousmigration to the KAO during the famine years of the Kalmyks living in other areas of the Russian Empire are investigated. The measures taken by the Soviet authorities on the organized relocation of groups of the Kalmyk population to the KAO in the 1920s are considered. They had to build and equip their lives almost from scratch, adapt to the unusual natural and climatic conditions of the territory. State assistance of financial and material order, support of fellow tribesmen in the KAO helped the Kalmyk migrants to quickly and less painlessly adapt to new living conditions. Kalmyk migrants from the first days after moving to KAO began to actively participate in the process of radical restructuring of the political and socio-economic systems of Kalmyk society, introducing their fellow tribesmen to a settled way of life, new forms of management. Today, most of their descendants live and work in the Republic of Kalmykia, an equal subject of the Russian Federation.